Fatores preditivos de descompensação da pessoa em situação crítica no serviço de urgência - Pinto, Ana Catarina (2021)
The signs of clinical deterioration are relatively similar between them and usually reflect the respiratory, cardiovascular and/or neurological systems collapse. It is essential that the nurses are able to keep in mind the several signs and symptoms that could be predictive of the deterioration of the patient admitted at the accident and emergency (A&E) department, in a way that they can reduce their mortality and morbidity. Aim: To understand the A&E nurses role in the identification of the patients at risk and to understand which are the predictive factors of deterioration identified by them. Methodology:  Exploratory-descriptive research gathered from qualitative data, through a Focus Group. Data were analyzed through Bardin´s Content Analysis. Results: The analysis of the data shows that it is essential to “Observe the patient” and to “attend data details” related with “behavioral and physical factors”. Conclusion: To be an A&E nurse demands a high level of competency, expertise and specialization that should be used to identify the signs and symptoms of clinical deterioration. To look at the patient and to value those observed data has a high impact at the Nurse Decision Making skills, promotes an early intervention and, consequently, reduces the A&E Patients mortality and morbidity.